Polimorfismos dos genes SLC11A1 e DLA-DRB1 e susceptibilidade de cães à leishmaniose - Ribeiro, Érica de Souza [UNESP] (2011)
The importance of visceral leishmaniasis in the context of public health has increased in the last decade. The manifestation of visceral leishmaniasis in dogs is variable and genetic studies and its relationship with visceral leishmaniasis have shown some candidate genes involved in susceptibility and resistance to this disease. This study aimed at evaluating the relationship between polymorphism of the genes Slc11a (solute carrier family 11 member 1), and DLA-DRB1 (dog leukocyte antigen) and the positivity to leishmaniasis determined by the amplification of Leishmania sp. kinetoplast DNA by PCR and the presence of anti-Leishmania sp. the indirect ELISA. We observed statistically significant associations between the leishmaniasis positive diagnosis and i. the presence of intron 1 microsatellite region alleles (141, 145 or 149) (P<0.0001), ii. the variation on the guanine number (8 or 9) in the promoter region (P=0.0280) (in both cases when analyzed separately), iii. the presence any of the microsatellite alleles associated to 8 or 9 G in the promoter region (P=0.0025). Microsatellite allele 141 was associated to negativity to leishmaniasis (P<0.0001). There was no association between the presence of any of the exon 2 DLA-DRB1 alleles and the leishmaniasis positive animals, although significant association between the frequency of the alleles DRB1-W, DRB1*00101 or DRB1-T and negative results to leishmaniasis were observed. These might be potential markers for dog’s resistance to visceral leishmaniasis